(3GdLQO GdZGeOI aj bhGUe GdQGaVIs - (3CMeO Hf YeQ GHf HgdjbG GdObGb, GHf HgdjbG GdObGbs
(3ChdgG (B:s
(3hcfJ hbaJ Ydi cJGH jTJed Ydi eSGFd GdQGaVI hbO Jcde YdjgG CHh YKeGf YeQh Hf HMQ GdLGMX cdGeG eGO Cf jNQL ajg Yf GdbUO aQCjJ Cf GNJUQ ef CUhd Pdc aUhdG s
(3BNQgG (B:s
(3BNQ GdcJGH hGdMeO ddg hMOgq s
(3CUdg ddLGMX aj NeSI CLRGAs
(3hQO HEjVGM Gdecfhf HOhf fSHI deDdas
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B3 - (3U (B361s
Keywords: (3GdJhMjO hGdedd hGdfMds